Borrowers under water! Rare disasters, regional banks, and recovery lending - Koetter, Michael; Noth, Felix; Rehbein, Oliver (Journal of Financial Intermediation, 2020)
We show that local banks provide corporate recovery lending to firms affected by adverse regional macro shocks. Banks that reside in counties unaffected by the natural disaster that we specify as macro shock increase lending to firms inside affected counties by 3%. Firms domiciled in flooded counties, in turn, increase corporate borrowing by 16% if they are connected to banks in unaffected counties. We find no indication that recovery lending entails excessive risk-taking or rent-seeking. However, within the group of shock-exposed banks, those without access to geographically more diversified interbank markets exhibit more credit risk and less equity capital.